Avaliação energética da produção de etanol utilizando como matéria-prima a cana-de-açúcar - Salla, Diones Assis; Badiz Furlaneto, Fernanda de Paiva; Cabello, Cláudio [UNESP]; Dias Kanthack, Ricardo Augusto (Universidade Federal de Santa Maria (UFSM), 2009)
This research analyzed the energetic consumption of the etanol, using as raw-material sugar cane. The searches were carried out from the field in the Midle Paranapanema River Region, São Paulo state, in the period from January to December 2007. The referring energy consumption from the crop production phase and industrial processing were evaluated. It was verified that the total energetic cost of the crop production corresponded to 14370.9MJ ha(-1), and the most onerous item was the inputs (50.4%). In the industrial step, the energetic consumption was equivalent to 1,641.56MJ t(-1), The 'hydrolysis, saccharification and broth treatment operations' represented 71.72% of the total energetic expenditure. It was also observed an energetic cost of 2.0MJ L(-1) in relation to the etanol produced in the main crop production operations, and 19.4MJ L(-1) in the industrial processing. The energy efficiency observed in the crop production and industrialization were of 1.1.
Energy evaluation of the etanol production using as raw-material the sugar cane
Keywords: Saccharum spp.; environmental sustainability; renewable energy; agricultural production; industrial processing